2015
DOI: 10.1080/09168451.2014.972324
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin enhances the production of major structural components of elastic fibers, elastin, and fibrillin-1, in normal human fibroblast cells

Abstract: Curcumin is the major component of the yellow extract derived from the rhizome of the Curcuma longa, which is also a main bioactive polyphenol and has been generally used as a spice, food additive, and herbal medicine. In this presented study, we found that curcumin can enhance the production of major structural components of elastic fibers, elastin, and fibrillin-1, in normal human fibroblast cells via increasing ELN and FBN1 promoters’ activities. With 2 μM curcumin treatment, the enhanced tropoelastin and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The cells incubated as above were plated at a density of 2000 cells/well (cancer cells) [ 18 , 41 , 42 ] or 10,000 cells/well (Detroit 551) on a 96-well plate for 24 h; serial dilutions of indicated compounds were added and incubated for additional 72 h. At the end of the incubation, cell viability was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT). The MTT formazan crystals were dissolved by DMSO, and the absorbance at 570 nm using a microplate spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA) [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cells incubated as above were plated at a density of 2000 cells/well (cancer cells) [ 18 , 41 , 42 ] or 10,000 cells/well (Detroit 551) on a 96-well plate for 24 h; serial dilutions of indicated compounds were added and incubated for additional 72 h. At the end of the incubation, cell viability was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT). The MTT formazan crystals were dissolved by DMSO, and the absorbance at 570 nm using a microplate spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA) [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, the cells were lysed with 100 μL of DMSO, and the absorbance was measured spectrophotometrically at 540 nm using an ELISA reader. The inhibitory concentration value at 50% cell viability is defined as IC 50 [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Waqas et al [70] used an elastometer to confirm the anti-ageing and elasticity-inducing effect on the skin following treatment with a cosmetic formulation containing soybean extract. Lee et al [71] suggested curcumin as a potential cosmetic ingredient after observing that it increases the expression of tropoelastin in human dermal fibroblasts.…”
Section: Cosmetics and Photoageingmentioning
confidence: 99%